Assessment of the роtеntiаl fоr thе formаtіоn аnd dеvеlорmеnt оf а сlustеr оf construction materials in Аstana (Journal of Economic Research & Business Administration, 2024)
The article conducted a study to assess the potential for introducing and developing clusters in the production of construction materials based on the economy of the city of Astana, and the significance of the study was reflected in determining and proving the advantages of the clustering system in this area. The purpose of the scientific work is to study theoretical principles and develop practical recommendations for improving the competitiveness of the regional economy on the example of Astana through the mechanism of creating and developing clusters for the production of construction materials.In the course of the study, such specific methods as general methods of economics, economic and statistical analysis, critical calculations, functional analysis and system direction were used. The theoretical foundations of the study are methodological concepts, scientific works and quantitative data of national statistics of various scientists, researchers on the implementation and development of the cluster system in the industry economy. Also, based on them, in order to achieve qualitative research results, such estimated indicators as localization coefficients, per capita production coefficients and specialization coefficients were calculated.The results obtained confirm the effectiveness of the implementation of the clustering system for the production of building materials in the development of the economy of Kazakhstan, which is reflected in the example of the city of Astana. Evaluation of performance indicators made it possible to substantiate the presented concepts and prove their practical significance.According to the authors, the results of the study can be effectively used in research work when solving the issues of clustering the construction industry in the development of the region. The key findings and these specific recommendations can serve as a basis for preparing development plans and strategies aimed at improving the competitiveness and efficiency of enterprises and organizations in the construction industry.Key words: cluster, cluster of production materials, localization coefficient, per capita production coefficient, specialization coefficient.